Naturally occurring volatile organic compounds in deep bedrock groundwater - Riikka Kietäväinen; Mari Nyyssönen; Maija Nuppunen-Puputti; Malin Bomberg (Communications Earth & Environment)
Abstract In deep continental bedrock groundwater, volatile organic compounds pose intriguing questions about their occurrence. Although their natural sources remain poorly characterized, they potentially have profound effects on global elemental cycles and safety assessment of underground facilities. Our investigation focused on non-methane volatile organic compounds in five groundwater-filled Precambrian bedrock fracture zones at 500 m to 2300 m depth in the Outokumpu Deep Drill Hole, Finland. The system revealed a range of indigenous volatile organic compounds, including alcohols, ketones, aldehydes, alkanes, aromatics, and sulfur-compounds. Metagenomic sequencing demonstrated spatially widely distributed genetic potential for microbial volatile organic compound metabolism. Integrating these findings with local geology and hydrogeochemistry, our results suggest that volatile organic compounds are not only formed in or released to groundwater but also degraded in the continental bedrock through interconnected abiotic and biotic processes.